Flood Simulation Models for a River System in a Tropical Region: The Case of Linggi River, Malaysia - Mohammed, Thamer Ahmed (1998)
Flooding of a river system in a tropical region is predicted using mathematical simulation models in this study. The proposed models were categorized as hydrologic model, hydraulic model and sedimentation model. Two methods of hydrologic models were used to simulate the peak: streamflow in a river system of a tropical region. The first hydrologic model is the river model, which is a first order linear autoregressive model, AR(1). The second hydrologic model is called the basin model which is a deterministic model based on a linear relationship between rainfall and runoff. The basin model is also described as a distributed model in which the river basin is divided into a number of subbasins whereby the rainfall and the runoff at each subbasin is simulated separately and then combined to get the river basin response. The Linggi River system in Seremban, Malaysia was used as a case study. The Linggi River system consists of a main river which is called Linggi, and it's six tributaries called the Batang Penar, Paroi, Temiang Diversion, Temiang, Anak Rasah and Kepayang. The total catchment area of the Linggi River system up to the point of interest is 127.7 km2. Recorded hydrologic data for the Linggi River basin was used in the evaluation and testing of the proposed models. Models evaluation involved calibration, verification and sensitivity analysis. Models testing was implemented using the Theil's technique. The calculated value of Theil's coefficient was 0.028, 0.17 and 0.01 for the basin model, river model and the hydraulic model respectively. A computer program was written to especially perform the calculations of the basin model. This computer program is called BSHYMD.